THE ROLE OF ENGLISH IN THE HOSPITALITY INDUSTRY: A LINGUISTIC PERSPECTIVE FROM HOTELS IN BANYUWANGI - Anam, Nurul; Putriana, Widhya (Consilium: Education and Counseling Journal, 2025)
The hospitality industry relies extensively on effective communication, with English proficiency serving as a cornerstone for delivering high-quality services to international guests. This qualitative research investigates the role of English in hospitality communication, adopting a linguistic perspective and focusing on three star-rated hotels in Banyuwangi, Indonesia. Through interviews, observations, and document analysis, the study explores the use of English in daily hotel operations, identifies common communication challenges, and proposes language development strategies. The findings reveal that employees face issues such as limited vocabulary, pronunciation difficulties, and cultural misunderstandings, all of which affect guest satisfaction and service delivery. The study recommends the implementation of English for Specific Purposes (ESP) training tailored to hospitality settings, emphasizing real-life scenarios, cultural awareness, and confidence-building. Enhancing English proficiency among hotel staff can significantly contribute to improved service quality and the global competitiveness of Banyuwangi's tourism sector.